PREVALENCE AND HISTOPATHOLOGY OVERVIEW OF SKIN TUMORS IN DOGS IN DENPASAR - Mango, Edward Emanuel; Kardena, I Made; Supartika, I Ketut Eli (Buletin Veteriner Udayana, 2016)
Skin tumors grow uncontrollably, invades the skin or soft tissue under the skin, can be benign or malignant. This research was conducted by analyzing risk factors : age and type associated with histopathological changes of 113 samples of dogs with skin tumors in Denpasar  in 2008-2012 are diagnosed from the Laboratory Pathologic of Balai Besar Veteriner in Denpasar Bali. From this study, it’s identified 15 types of skin tumors in dogs in Denpasar, with respective prevalence were lipoma 28.32%,  histiocytoma 10.62%, squamous cell carcinoma 8.85%,lymphosarcoma 6.19%, melanocytoma 6.19%, sebaceous gland tumors 6.19%, fibroma 5.31%,fibrosarcoma 5.31%, hemangioma 4.42%, hemangiosarcoma 4.42%, trichoepthelioma 4.42%,perianal gland adenoma 3.54%, liposarcoma 2.65%, mastocytoma 2.65%, and papilloma 0.88%.Prevalence of skin tumor in dogs in Denpasar based on the breeds and age’s wasn’t significantly different, it means skin tumor can spread either local and non local breed dog’s and can infect allages in dog’s. The histopathological changes from each kinds of skin tumors was different depended from the type of cells that grew uncontrollably, however generally they had  unregulated structure with differential cell in various levels in chromatin, nucleus, and cytoplasmic.
Keywords: prevalence; histopathology; skin tumors; dog